Eleventh Five Year Plan 2007-12 Annual Plan 2007-08 Government of Punjab Department of Planning - Planning Commission (Planning Commission, 2007)
The economy of Punjab has traditionally revolved around its success in the agriculture sector. Since the Green Revolution in the 1960s, Punjab has taken major strides in increasing agricultural productivity and has the unique distinction of contributing the maximum quantities (75% wheat and 30% rice during marketing season 2006-07) to the central pool of foodgrains. Almost two decades of militancy in the State, however, retarded the expansion of the manufacturing sector in the State while some of its neighbouring States expanded their industrial production given their locational advantages or a more conducive policy regime. The strategy of increased foodgrains production also brought along its concomitant problems, viz. depletion of ground water resources and soil nutrient imbalance. Thus the present agricultural system is increasingly becoming ecologically and even economically untenable. Punjab’s hopes for sustaining its position as a front-runner State in economic growth thus hinges on achieving a “second breakthrough in agriculture” as well as successfully expanding its manufacturing and services sector. Diversification of agricultural production patterns, agri-processing and marketing has, therefore, rightly come to acquire prominence in the Government’s planning process in the recent years.
Eleventh Five Year Plan 2007-12 & Annual Plan 2007-08
Government of Punjab